Інвестиційна привабливість інноваційних проектів - Усов, Максим Анатолійович; Гаврись, Ольга Олександрівна; Сусліков, Станіслав Вячеславович (Класичний приватний університет, 2019)
Інвестиційна привабливість – це сукупність факторів, аналіз яких вказує на можливість вкладання коштів в той чи інший об'єкт і отримання певного ефекту від здійсненої операції. В статті представлено організаційну схему учасників управління конкурентоспроможністю інноваційних проектів на основі досягнення взаємодії оцінки інвестиційної привабливості підприємства, що впроваджує інновації, і реалізованих ним завдань. Виділено ряд переваг над конкурентами, які потенційно може мати підприємство в ході реалізації інноваційного проекту. Запропоновано створення на підприємстві ради з інноваційних проектів, що є першою необхідною сходинкою перебудови структури управління для прискорення і підвищення ефективності інноваційно-інвестиційної діяльності. Перераховано обов'язки, а також переваги та недоліки інноваційних рад. Сформовано механізм поетапного управління конкурентоспроможністю інноваційного проекту.

Investment attractiveness is a combination of factors, the analysis of which indicates the possibility of investing in a particular object and obtaining a certain effect from the operation. The object of the article is to substantiate the practical recommendations for the formation of a mechanism of stage-by-stage management of innovative projects competitiveness, which are intended to increase their attractiveness for potential investors. The substantial amount of scientific work of Ukrainian and foreign scientists of various economic schools is devoted to issues of ensuring the investment attractiveness of enterprises. They investigated various aspects of this problem; in particular, they theoretically substantiated the investment attractiveness of an enterprise as an object of management, and paid considerable attention to assessing the investment attractiveness of enterprises. At the same time, issues of an applied nature remain insufficiently covered, in particular, the formation of a mechanism for the phased management of the competitiveness of innovative projects, which will increase their investment attractiveness. In this article the organizational chart of the participants of the competitiveness management of innovative projects on the basis of achieving the interaction of assessing the investment attractiveness of an enterprise, which implement innovations and the tasks accomplished by it, is presented. A number of advantages over competitors, which a company may potentially have during the implementation of an innovative project, are highlighted. The creation of an innovative council at the enterprise is suggested. Responsibilities, as well as advantages and disadvantages of innovative council are listed. The basis for the establishment of a mechanism for the phased competitiveness management of an innovation project is laid down. Creation of innovative councils is the first stage of the transformation of the traditional management structure of enterprises, which is intended to increase the success of the implementation of innovations. The proposed creation of an innovative council at the enterprise is the first necessary step in restructuring the management structure to accelerate and increase the efficiency of innovative and investment activities.
Investment attractiveness of innovative projects
Keywords: інвестиції; інноваційно-інвестиційний процес; інвестиційний клімат; інноваційна рада; конкурентоспроможність; інвестиційна привабливість; investment attractiveness; innovative project; competitiveness; investment; innovative council